Guidelines to Mathematics, K-6. Key Content Objectives, Student Behavioral Objectives, and Other Topics Related to Elementary School Mathematics - Chandler, Arnold M.; Wisconsin State Dept. of Public Instruction, Madison ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
GRADES OR AGES: K-6. SUBJECT MATTER: Mathematics. ORGANIZATION AND PHYSICAL APPEARANCE: The guide is divided into several chapters. The central and longest chapter, which outlines course content, is further subdivided into 15 units, one for each of 15 content objectives. This chapter is in list form. The guide is offset printed and staple-bound with a paper cover. OBJECTIVES AND ACTIVITIES: The central chapter lists 15 mathematical concepts such as numeration systems, ratio and proportion, size and shape, or measurement. A list of related behavioral objectives for each concept at each grade level is then presented. No specific activities are mentioned, although one short chapter gives general guidelines on developing problem-solving situations. INSTRUCTIONAL MATERIALS: A short bibliography lists several references for each chapter. STUDENT ASSESSMENT: A chapter on evaluation and testing gives guidelines for developing tests and choosing appropriate methods for different grade levels. (RT)
ERIC Note: Bulletin No. 141.
Educational level discussed: Elementary Education.
Educational level discussed: Grade 1.
Educational level discussed: Grade 2.
Educational level discussed: Grade 3.
Educational level discussed: Grade 4.
Keywords: Curriculum Guides; Elementary Education; Elementary School Mathematics; Grade 1.; Grade 2.; Grade 3.; Grade 4.; Grade 5.; Grade 6.; Kindergarten; Mathematics Curriculum